Non-equilibrium thermodynamics and statistical mechanics foundations and applications - Attard, Phil. (Oxford : Oxford University Press, 2013)
This title builds from basic principles to advanced techniques and covers the major phenomena, methods, and results of time-dependent systems. It is a pedagogic introduction, a comprehensive reference manual, and an original research monograph.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Oct. 31, 2012).
Keywords: Nonequilibrium thermodynamics; Nonequilibrium thermodynamics -- Statistical methods; Nonequilibrium statistical mechanics